A critical review on tackling complex rare earth supply security problem. (August 2022) - Salim, Hengky; Sahin, Oz; Elsawah, Sondoss; Turan, Hasan; Stewart, Rodney A.
Abstract: A sustained and guaranteed supply of rare earth (RE) minerals is imperative to a country's national security to sustain its manufacturing, defence, and high-tech industry sectors. Although the term is referring to "rare", it does not mean that they are not abundant, but rather the difficulties to extract these minerals and the highly mixed nature of the deposits make them rare. RE minerals' production has been closely monopolised by Chinese mining companies which have create concerns on their supply risk and resilience in the future. This study critically reviewed 1) the existing approaches and theories used to evaluate the RE supply security and 2) the pathways to achieve RE supply security and their existing drivers and barriers to implementation. Literature and reports were collected from Web of Science, Scopus, and Google search which resulted in 323 articles included in the final database and 67 articles for the critical analysis. Our findings indicate the need to integrate existing approaches and theories such as resilience, material criticality, and risk theory to overcome their individual limitations. This study also suggested four pathway categories that can improve RE supply security including 1) circular economy strategies, 2) supply chain agility, 3) building domestic supplies, and 4) exploring beyond terrestrial mining. A preliminary causal loop diagram (CLD) was developed based on the factors identified during the review to depict the complexity and dynamics of the different system elements affecting the RE supply security. Highlights: 323 articles and reports on rare earth supply security were critically reviewed. Risk theory, material criticality and resilience theory were discussed. Four pathway categories and their drivers and barriers were discussed. An initial causal loop diagram was developed to depict the system complexity.